Self-assessment and learning motivation in emergency point-of-care ultrasound: an online pilot investigation in German physicians - Joachim Bansbach; Michael Bentele; Matthias Bollinger; Stefanie Bentele; Ronny Langenhan; Bianka Gerber; Milena Trifunovic-Koenig; Stefan Bushuven (BMC Emergency Medicine)
Abstract Introduction Learning motivation is essential to obtain and maintain ultrasound competencies in emergency medicine. One’s competencies herein and the need for ongoing training are best evaluated by self-assessment. This may be flawed by overconfidence effects - the belief to be better than others or better than tests reveal. This study aims to clarify the underinvestigated interaction of learning motivation and self-assessment in emergency point-of-care-ultrasound (POCUS). Methods In this cross-sectional multicenter project, physicians assessed their own and others’ competence and learning motivation using the Situational Motivation Scale comprising intrinsic motivation, external and identified regulation, and amotivation. In addition, we presented eight ultrasound loops of different pathologies to emergency physicians of various specialties. Results Overall, the motivation to learn was high, while self-assessment showed no significant overconfidence in POCUS. The rate of correct diagnoses based on the loops was relatively low. As a result, we did not detect overconfidence effects in participants who completed questions (n = 86) and tests (n = 56). Overplacing oneself above peers negatively correlated with intrinsic learning motivation and identified regulation and positively correlated to amotivation. Further analyses indicated that learning motivation was associated with the interactions of the physicians’ risk perception, speciality, and self-assessment. Discussion The absence of overconfidence effects, the complexity of learning motivation and their interaction show that prior findings in other contexts may not be easily transferable to POCUS and could be highly context-sensitive. In conclusion, this study highlights high levels of learning motivation but relatively low diagnostic accuracy in POCUS, which suggests the need for ongoing education and assessment. Ensuring that physicians continue to receive objective feedback and opportunities to refine their skills is critical for maintaining high standards of care. Despite the small sample size and other limitations of the study, the results primarily served to generate hypotheses for future research on emergency ultrasound education.